Step-by-step monitoring of CVD-graphene during wet transfer by Raman spectroscopy. Issue 71 (16th December 2019) - Wu, Zehao; Zhang, Xuewei; Das, Atanu; Liu, Jinglan; Zou, Zhenxing; Zhang, Zilong; Xia, Yang; Zhao, Pei; Wang, Hongtao
Abstract : The quality evolution of as-grown graphene during wet transfer from Cu to SiO2 /Si substrate is investigated by Raman spectroscopy and the relavant factors during this process are identified. Abstract : Transfer acts as a crucial bridge between the chemical vapor deposition (CVD) synthesis of large-scale graphene and its applications, but the quality evolution of a graphene film during transfer remains unclear. Here we use scanning Raman spectroscopy to monitor as-grown graphene during each step of wet transfer including floating on etchant solution, loaded onto a target substrate, and with additional annealing. Results show that the etchant solution results in strong compressive strain and p-type doping to floating graphene, but both are significantly reduced after the sample is loaded and rinsed especially for the doping. An annealing treatment increases the compressive strain in graphene but hardly its doping level. Moreover, when a poly(methyl methacrylate) (PMMA) layer is used to assist the transfer, it does not only increase the p-type doping of floating graphene but also lowers the crystalline quality of annealed graphene. Therefore, to obtain graphene with better quality, besides the attempts of improving CVD synthesis for its larger domain sizes, universal and easy-to-use polymer-free transfer techniques must be developed as well.